Vulnerable Mission in Depth: Listening to God and Man in Indonesia - Jusuf Hutapea; Natanael Winanto; Marthin Steven Lumingkewas (Sekolah Tinggi Teologi Widya Agape dan Perkumpulan Teolog Agama Kristen Indonesia, 2025)
The Christian mission in Indonesia faces significant challenges amid the country's cultural, religious, and social diversity. With a majority Muslim population, it is crucial for the church to listen to both the voice of God and the voice of humanity in carrying out its mission. This study aims to explore how the Christian mission can be more effective by integrating these two aspects: listening to the voice of God through spiritual teaching and addressing the social needs of the community. The concept of a vulnerable mission, which prioritizes responsiveness to social and cultural challenges, forms the basis of this study. The research method used is a qualitative approach with a case study design, involving in-depth interviews with church leaders, missionaries, and community members, as well as document analysis to understand the application of both aspects in the diverse Indonesian context. The research findings indicate that successful Christian missions in Indonesia are those that can integrate spiritual aspects with social empowerment, thereby strengthening the church's relationship with the local community. The contribution of this research is the development of mission theory with a more inclusive and culturally sensitive approach. These findings are expected to provide insights for churches in Indonesia and similar countries in designing more adaptive, holistic, and relevant mission strategies.